Spreading depolarizations in patients with spontaneous intracerebral hemorrhage: Association with perihematomal edema progression. Issue 5 (May 2017) - Helbok, Raimund; Schiefecker, Alois Josef; Friberg, Christian; Beer, Ronny; Kofler, Mario; Rhomberg, Paul; Unterberger, Iris; Gizewski, Elke; Hauerberg, John; Möller, Kirsten; Lackner, Peter; Broessner, Gregor; et al.
Pathophysiologic mechanisms of secondary brain injury after intracerebral hemorrhage and in particular mechanisms of perihematomal-edema progression remain incompletely understood. Recently, the role of spreading depolarizations in secondary brain injury was established in ischemic stroke, subarachnoid hemorrhage and traumatic brain injury patients. Its role in intracerebral hemorrhage patients and in particular the association with perihematomal-edema is not known. A total of 27 comatose intracerebral hemorrhage patients in whom hematoma evacuation and subdural electrocorticography was performed were studied prospectively. Hematoma evacuation and subdural strip electrode placement was performed within the first 24 h in 18 patients (67%). Electrocorticography recordings started 3 h after surgery (IQR, 3–5 h) and lasted 157 h (median) per patient and 4876 h in all 27 patients. In 18 patients (67%), a total of 650 spreading depolarizations were observed. Spreading depolarizations were more common in the initial days with a peak incidence on day 2. Median electrocorticography depression time was longer than previously reported (14.7 min, IQR, 9–22 min). Postoperative perihematomal-edema progression (85% of patients) was significantly associated with occurrence of isolated and clustered spreading depolarizations. Monitoring of spreading depolarizations may help to better understand pathophysiologic mechanisms of secondary insults after intracerebral hemorrhage. Whether they may serve as target in the treatment of intracerebral hemorrhage deserves further research.